Pelajaran Sirah Rasul Di Sekolah Rendah Agama (SRA): Kajian Teroka Terhadap Sukatan Dan Keberkesanannya Di Daerah Sepang Selangor Darul Ehsan - Nidzamuddin Zakaria; Ahmad Kamel Mohamed; Abdulaziz Adel M (Universiti Sains Islam Malaysia, 2024)
This study focuses on the Sirah Rasul subject which is organised in Religious Primary Schools in Sepang, Selangor (SRA). This subject is aimed to support and strenghen the Islamic Education in the National Educational System of Malaysia. The main aspects of this study involve the curriculum, methods of teaching and learning and activities carried out by Education Department, Jabatan Agama Islam SeIangor (JAIS) and Sepang Islamic Religion District Office. The main concern of the research is to find out how far is the objective of these Sirah Rasul subjects have been achieved. Apart from that, it analyzes the Sirah Rasul curriculum and the effectiveness of that subject specifically in the research location. Thus, method of documentation, interviews, observation and questionnaires are used to gather the relevant data for this study. When all the data is analysed, this research finds out that the Sirah Rasul subject has given many positive effects to most of the SRA students in Sepang, Selangor in the understanding of the Sirah Rasul and the practising the Sunnah Rasul in the daily life. The findings of the study also show that the curriculum of the Sirah Rasul subject are not free from weaknesses and errors involving the textbooks of year three to year six a part of the lack of teaching aids and sources of references for the teachers involved. However, this recearch proves the Sirah Rasul subject should be continued for Sepang SRAs students and also in Selangor generally. It is suggested that the curriculum should be improved eventually in order to ensure the noble objective will be achieved in the future.